2016
DOI: 10.17159/2413-3108/2010/v0i34a873
|View full text |Cite
|
Sign up to set email alerts
|

‘When I see them I feel like beating them’: Corruption and the South African Police Service

Abstract: South African survey data on citizen attitudes towards police have, for the past ten years, indicated a lack of trust in law enforcers. Similarly, the SAPS has, since the early nineties, developed a public image as a widely corrupt organisation. In 2010 the SAPS reverted to military ranks and adopted a discourse of 'force' in an attempt to improve discipline, effectiveness and image. This paper presents a summary of findings from 15 focus groups conducted in mid-2010 that sought to explore public experiences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…The success of the 1994 commenced, ANC-led law enforcement makeover has however been considerably debated in the media (News24 2008(News24 , 2013IOLNews 2013) and among researchers (Bruce 2002;Bayley 2005;Faull 2010;Newham and Faull 2011;Kutnjak Ivković and Sauerman 2008 with mostly negative assessments on especially issues of police conduct and integrity. The ANC coalition 8 government itself is under even more scrutiny and criticism in terms of its questionable prevention of and dubious reactions to corruption from within its own ranks (see Bruce 2002;Van Vuuren 2004;Giliomee and Mbenga 2007;News24 2011;Transparency International 2013;Newham 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the 1994 commenced, ANC-led law enforcement makeover has however been considerably debated in the media (News24 2008(News24 , 2013IOLNews 2013) and among researchers (Bruce 2002;Bayley 2005;Faull 2010;Newham and Faull 2011;Kutnjak Ivković and Sauerman 2008 with mostly negative assessments on especially issues of police conduct and integrity. The ANC coalition 8 government itself is under even more scrutiny and criticism in terms of its questionable prevention of and dubious reactions to corruption from within its own ranks (see Bruce 2002;Van Vuuren 2004;Giliomee and Mbenga 2007;News24 2011;Transparency International 2013;Newham 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Not only was this new approach conflicting with the agency's initial reform focuses, but with the code of silence an expected consequence of militarized policing environments (Kutnjak Ivković and Sauerman 2008, p. 28), it is very likely that instead of "improving discipline," the strategy actually strengthened the code within the agency. Correspondingly, Faull (2010) warns that the SAPS should be careful that the "military ranks and 'war on crime' do not create police officials who alienate the citizens they serve" (p. 40).…”
Section: Resultsmentioning
confidence: 99%
“…An Afrobarometer study on corruption and the public service in South Africa indicated that more than 50% of the representative sample perceived ‘all’ or ‘most’ police officials to be involved in corruption (Wielders, 2013). In addition, focus-group data from studies undertaken in Cape Town, Durban and Johannesburg suggested that there was significant public tolerance of and complicity in police corruption (Faull, 2010b). In this regard, it has been suggested that the key risks for police corruption and related deviance have been the outcome of inadequate implementation of anti-corruption measures, due to organisational and managerial dysfunctionality (Faull, 2007; Newham and Faull, 2011), as well as the perverse effects of the SAPS’s performance-management system (which rewards police on the basis of reductions in recorded crime) (Faull, 2010a).…”
Section: Police Corruptionmentioning
confidence: 99%
“…Moreover, there is high discontentment among people (including university students) with the prevailing policing style in contemporary South Africa. The officials of the SAPS have been entangled in censurable misconducts, corruption, predatory policing and abuse of power (Burger, 2011;Faull, 2010). Besides the incessant daily reports of unpleasant public personal and vicarious experiences with the SAPS, there are also notable scandals and corrupt cases linked to police officers across the country (see Burger, 2011;Faull, 2010).…”
Section: Policing Students In Modern South Africa: Complexities and Dmentioning
confidence: 99%